Comparative analysis of the characteristics, care pathways, and outcomes of English and Welsh major trauma patients injured by high versus low energy transfer mechanisms in 2019 - Thomas A G Shanahan; Michael Tonkins; Omar Bouamra; Dhushy Surendra Kumar; Antoinette Edwards; Laura White; Anthony Kehoe; Jason E Smith; Timothy J Coats; Fiona Lecky (PLoS ONE, 2026)
Background Recent trends in high-income countries indicate a shift in the causes of major trauma, with low-energy transfer mechanisms, particularly falls from less than two meters, becoming increasingly prevalent. This study aimed to compare the demographics, care processes, and outcomes of major trauma patients injured by low and high-energy transfer mechanisms. Methods This comparative cohort study utilized anonymized data from adult patients recorded in the Trauma Audit and Research Network in 2019. Patients were categorized into low-energy (falls less than 2 meters) and high-energy (other mechanisms) groups. The study focused on patients with an Injury Severity Score (ISS) greater than 15. Data from up to 179 English and Welsh hospitals were included. Results In 2019, 53.6% (n = 16,087) of major trauma patients were injured by low-energy falls. When compared to the high-energy cohort, these affected older patients (median age 80 vs. 47 years; p < 0.001), with a higher prevalence of pre-existing comorbidities (90.4% [95%CI 89.9–90.8] vs. 56.2% [95%CI 55.4–57.0]; p < 0.001) and traumatic brain injuries (74.0% [95%CI 73.3–74.7] vs. 49.8% [95%CI 48.9–50.6]; p < 0.001). Low-energy fall patients were more likely to be initially treated in Trauma Units rather than Major Trauma Centres and received fewer interventions such as surgery and critical care admission. Low-energy falls patients had a higher in-hospital mortality rate (14.0% [95%CI 13.5% − 14.6%] vs. 10.3% [95%CI 9.8% − 10.8%]; p < 0.0001). Conclusions The increasing burden of major trauma from low-energy falls necessitates a re-evaluation of current trauma care systems and injury prevention strategies to better serve this distinct and growing patient population. Future research should focus on optimizing care pathways, defining patient orientated outcomes and improving outcomes for patients injured by low-energy falls.